COMPUTERIZED INFORMATION SYSTEM DATA RESIDENT ON RT. 007 / RW. 07 KEL. DURI KEPA - Achmad Faisal; Eko Hadiyanto SSi, MMSI. (Jurnal Sistem Informasi, 2002)
The author uses a government agency that provides services to the people who carriedout with various kinds of good that is given to members of the community andsociety in the region entrants.By using this computerized data then there are people who saved with the rapid datasearching process is done by computer people just by entering the data requiredcitizens. So that a lower error rate than manually, in case of errors may happen onlyin entering data to be processed and data faster and more accurate than manually.